ダイ 32 ジ ナンキョク チイキ カンソクタイ ショウワ キチ エットウ (1991) ホウコク - 藤井, 理行; フジイ, ヨシユキ; Fujii, Yoshiyuki (1992)
P(論文) 第32次南極地域観測隊越冬隊は, 昭和基地越冬31名, あすか観測拠点越冬8名, 合計39名により構成された。あすか観測拠点の越冬については別に報告されるが, 越冬の後1991年12月に一時閉鎖し, 5年間続いた越冬観測にピリオドを打った。昭和基地の運営は, 1991年2月1日から開始し1992年1月31日に終了した。この間, 昭和基地およびみずほ基地の施設の維持を行うとともに, 定常観測を継承し, さらに宙空系, 気水圏系, 生物・医学系による研究観測を実施した。研究観測としては, 気水圏系の「南極域における気候変動に関する総合研究(5年計画5年次)」と宙空系の「ポーラーパトロール気球による超高層大気の観測(3年計画の1年次)」などを実施した。また, 多目的衛星データ受信システムを利用して, あらたに欧州リモートセンシング衛星の受信も開始した。ドーム計画の準備およびみずほ基地の維持を目的に, 内陸旅行を実施し中継拠点を設置した。 The wintering party of the 32nd Japanese Antarctic Research Expedition performed its activities at two wintering sites from 1991 to 1992,consisting of 31 members at Syowa Station (69°00′S, 39°35′E) (leader : Yoshiyuki FUJII) and 8 members at Asuka Station (71°31.5′S, 24°8′E) (leader : Kazuo MAKITA). Wintering activities at Asuka Station will be reported separately. The main scientific research programs at Syowa Station were as follows; 1) Studies on ocean-atmosphere interaction in the sea ice area as part of the Antarctic Climate Research Program (ACR), 2) Environmental science studies, 3) Polar patrol baloon experiment and 4) Life science studies. Various airborne observations and inland glaciological traverses were carried out. departmental bulletin paper